Nghiên cứu tính chất lưu biến, độ bền oxi hóa nhiệt và độ bền dung môi của vật liệu nanocompozit PVC/DOP/khoáng sắt hữu cơ - Hoàng, Thái; Kim, Nguyễn Thạc; Thẩm, Đõ Quang; Hà, Nguyễn Thu; Kim Dung, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Poly(vinyl chloride)/dioctyl phthalate/organoclay nanocomposites with varied amounts of organoclay are prepared by melt intercalation. The rheological character of the composites is measured on rheometer C-VOR 150. The tensile strength (s) and the elongation at break (e) of the materials are determined with tester WPM. Their thermo-oxidative resistance is evaluated after testing the samples at 100oC in 168 hours. The solvent resistance of the materials is determined by immersing the samples in toluene - acetone mixture at room temperature in 168 hours. The obtained results show that the storage modulus and complex modulus of the materials with a small amount of organoclay are higher than those of the materials without organoclay and reach the maximal values at loading 1 wt.% organoclay. Generally, the thermo-oxidative resistance and solvent resistance of the composites containing organoclay are dramatically improved. Specially, the composite containing 1.5 wt.% organoclay has the best solvent resistance. The materials without organoclay have thermo-oxidation resistance lower than materials with different content of organoclay. These confirm the effective barrier ability of organoclay in PVC matrix.